Reliability of vestibular evoked myogenic potentials in healthy subjects - Suwicha Isaradisaikul (2018)
OBJECTIVE:: To analyze test-retest reliability of vestibular evoked myogenic potential (VEMP) responses with and without the use of electromyography (EMG) monitoring in people with normal audiovestibular function. PATIENTS:: Twenty adult volunteers with no history of ear disease, normal otoscopic examination, normal pure-tone audiometry thresholds, and normal tympanograms. INTERVENTIONS:: Prospective evaluation of VEMP responses with and without the use of EMG monitoring in 2 separate sessions 1 to 4 weeks apart. MAIN OUTCOME MEASURES:: Threshold repeatability, p13 and n23 latency, p13-n23 interlatency, and interamplitude and interaural amplitude difference from the first and the second sessions were assessed via the intraclass correlation coefficient. RESULTS:: Test-retest reliability of p13-n23 interamplitude was found to be excellent, and the reliability of threshold and latency was found to be fair to good (with the exception of poor reliability for p13 latency in the EMG monitoring condition). CONCLUSION:: Overall, VEMP response parameters were found to have fair to good test-retest reliability. The intraclass correlation coefficient value for amplitude was found to be more reliable than latency, with the latency of n23 more reliable than the latency of p13. Clinicians should consider these findings when interpreting VEMP responses. Maintenance of symmetric head rotation with and without EMG monitoring produced reliably reproducible results, the VEMP amplitude being the best criteria. © 2008, Otology & Neurotology, Inc.